Footwear technology and biomechanical adaptations in ultramarathon running: a PRISMA-Guided narrative review integrating direct and laboratory evidence - Waśkiewicz, Zbigniew; Akbaş, Anna; Grzywacz, Tomasz; Borysiuk, Zbigniew (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundFootwear influences biomechanical strategy, fatigue response, and performance outcomes in trail and ultramarathon running. Yet, much of the current evidence remains fragmented across isolated laboratory trials and small-scale field studies.ObjectiveThis review synthesizes findings from 20 verified studies and one preprint to examine how footwear properties—such as midsole cushioning, longitudinal bending stiffness (LBS), heel-to-toe drop, and shoe mass—influence running economy, gait mechanics, and fatigue-related adaptations in prolonged trail environments.MethodsA systematic synthesis was conducted across experimental, observational, and in-race studies involving trail or ultramarathon runners. Studies that assessed biomechanical, performance, or fatigue-related outcomes in the context of footwear design and terrain were included.ResultsFootwear design was found to affect running economy and mechanical loading significantly, but the magnitude and direction of these effects were highly context-dependent. Stiffer shoes with advanced midsole geometry improved energy efficiency in trained runners under controlled conditions, while more compliant foams offered protective benefits during downhill and prolonged efforts. Foot strike patterns shifted dynamically in response to terrain slope and fatigue, with flatter landings and increased step frequency emerging as common compensatory strategies. Importantly, shoe materials degraded under racing conditions, altering their functional properties during the event.ConclusionThere is no universally optimal shoe for trail and ultramarathon running. Instead, performance and protection depend on how footwear features align with individual biomechanics, terrain demands, and the capacity for gait adaptation under fatigue. These findings support a move away from categorical shoe labels toward personalized, terrain-aware footwear strategies that evolve with the runner and the race. In practice, this means that athletes and coaches should prioritize adaptability across terrain and fatigue states rather than seeking a universally superior footwear model.